2017
DOI: 10.1007/s11605-017-3518-7
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Artificial Neural Networks in Predicting Pancreatic Cancer Survival

Abstract: ANN models can accurately predict the 7-month survival of pancreatic adenocarcinoma patients, both with and without resection, at a 91% sensitivity and 38% specificity. This implies that ANN models may be useful objective decision tools in complex treatment decisions. This information may be used by patients and surgeons in determining optimal treatment plans that minimize regret and improve the quality of life for these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…R 2 was reported in one study 19. Sensitivity and specificity were also poorly reported (n=2) 26 29. Internal validation was rarely performed.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…R 2 was reported in one study 19. Sensitivity and specificity were also poorly reported (n=2) 26 29. Internal validation was rarely performed.…”
Section: Resultsmentioning
confidence: 99%
“…The number of model development studies, with (n=3)18–20 and without (n=12) external validation,21–32 increased sharply in recent years (figure 2). Multivariable Cox regression proportional hazard regression was the most commonly employed modelling method (n=13)18–25 27–29 31 32 with two studies employing alternative machine learning techniques (Bayesian model: n=1; Artificial Neural Network (ANN): n=1) 26 30. Six models could be applied preoperatively 19 23 24 27 28 31.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, if RFA were applied in PC, the results showed complication rates (15%) and a progression-free survival rate of 22% during the follow-up of 12 months [ 35 ]. Previous studies showed that the proportion of 7-month survival in PC patients in resection and no resection group was 53.19% versus 70.40% [ 36 ], and the 12-month overall survival in the radiation and nonradiation group was 43% and 29%, respectively [ 37 ]. In fact, as an emerging technique, IRE was usually conducted percutaneously or by open surgical or laparoscopic access, which was superior in unresectable lesions.…”
Section: Discussionmentioning
confidence: 99%